Festivals and tourism development: Examples from Tanzania and Zimbabwe - Batinoluho, Ladislaus; Basera, Vitalis (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2022)
This study examines the impact of festivals in developing tourism in Zimbabwe and Tanzania borrowing experience from the two countries and other countries. The significance of festivals in development of tourism is relentless. The study identified major festivals and their importance. Festivals are gradually turning out to be arenas of discussions aiding people to prompt their understandings on broader social, political and cultural issues. Festivals are part of the most significant products of tourism, nonetheless also crucial component of humanity. This study is descriptive by design and it synthesizes published journal articles, books, magazines and newspapers. Correspondingly, the research employed Google scholar to search for the keywords to gain access to different information on the subject. The study also applied content analysis to evaluate the idea of festivals in relation to tourism. The study reveals that festivals have enormous contribution in the growth and development of tourism sector. Festivals draw tourists, where in turn tourists spend money, which enhances the local economy equally on and off the festival place. On-place spending comprises parking fees for those with vehicles, food (game meat), beverage, soft drinks, shopping and souvenir sales. Festivals in the tourism sector have ability to build relationship especially in the festival planning stage, during and after. The study further found that festivals form an opportunity to a group to induce their preference and belief. Crucial investigation of the impact of festivals in tourism development presented that festivals are one of the great vital tourism products, but also essential ingredient of society. This research shows that festivals have important contribution in growth of tourism. This study highlights the potentials of festivals in diversifying tourism products. The paper is based only on literature review to arrive at conclusion and the literature is relatively old. Survey method can be used for broader appreciation of festivals in the countries.